Analisis Pengaruh PDB Perkapita, Pengeluaran Pemerintah, dan Pengangguran terhadap IPM di Negara-Negara ASEAN Tahun 2009-2018 - Ardiansyah Dewa Astana Wiguna; Deden Dinar Iskandar (Diponegoro Journal of Economics, 2021)
Human Development Index (HDI) is one indicator of development progress on aspects of human quality in a country. This research aims to analyze the effect of PDB percapita, government expenditures, and unemployment against HDI in ASEAN’s countries. The analytical method used in this research is random effect model (REM). This research used secondary data in panel form containing 6 Countries at ASEAN on cross section data and 2009 until 2018 on time series data. Data processed with Eviews10. The result of this examine shows that GDP percapita and government expenditures has positive and significant effect for HDI in ASEAN. Meanwhile, unemployment are insignificant for HDI in ASEAN.